2013
DOI: 10.3168/jds.2012-6324
|View full text |Cite
|
Sign up to set email alerts
|

Genomic architecture of bovine κ-casein and β-lactoglobulin

Abstract: The objective of this study was to characterize the genetic architecture underlying the absolute concentrations of 2 important milk proteins, κ-casein (κ-CN) and β-lactoglobulin (β-LG), in a backcross population of (Holstein × Jersey) × Holstein cattle. A genome-wide association analysis was performed using a selective DNA pooling strategy and the Illumina BovineHD BeadChip assay [777,000 (777K) SNP markers; Illumina Inc., San Diego, CA]. After correction for multiple testing, 25 single nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 44 publications
5
30
1
2
Order By: Relevance
“…Because this SNP is located within the region identified on BTA 13, the effect of the relative concentration of κ-CN on rennet-induced gelation could be strengthened. In addition, Gambra et al (2013) identified 25 SNP associated with the absolute concentration of κ-CN, and especially, one of the SNP could be of interest in relation to findings in the present study. The interesting SNP is located in the MTUS1 gene within the genome-wide significant region on BTA 27.…”
Section: Confirmation Of Associated Genomic Regionssupporting
confidence: 61%
See 2 more Smart Citations
“…Because this SNP is located within the region identified on BTA 13, the effect of the relative concentration of κ-CN on rennet-induced gelation could be strengthened. In addition, Gambra et al (2013) identified 25 SNP associated with the absolute concentration of κ-CN, and especially, one of the SNP could be of interest in relation to findings in the present study. The interesting SNP is located in the MTUS1 gene within the genome-wide significant region on BTA 27.…”
Section: Confirmation Of Associated Genomic Regionssupporting
confidence: 61%
“…The fixed effect of the significant haplotype has a large negative effect on G 30 , and it was found to explain 7.7% of the phenotypic variation of the trait. The overlap between the study by Gambra et al (2013) and the present study indicates that a gene affecting the concentration of κ-CN might be responsible for the QTL within this location.…”
Section: Confirmation Of Associated Genomic Regionscontrasting
confidence: 46%
See 1 more Smart Citation
“…During the past years, several whole-genome scans and genome-wide association studies (GWAS) have been conducted for milk composition traits (e.g., Schopen et al, 2009;Gambra et al, 2013), but such studies are scarce for technological properties of milk. Thus far, only chromosomal regions affecting rennet-induced coagulation important for cheese production have been studied (Gregersen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental material is available online at www.g3journal.org/lookup/suppl/ doi:10.1534/g3.116.031096/-/DC1 1 into three domains: biological processes, molecular functions, and cellular components. This ontology has been used successfully for dissecting relevant traits in livestock species (e.g., Peñagaricano et al 2013;Gambra et al 2013). Similarly, each MeSH term is clustered into 19 different categories; some MeSH categories, such as Diseases, are not included in GO, whereas other functional categories, such as Phenomena and Processes, or Chemicals and Drugs, share similar concepts with those of GO.…”
mentioning
confidence: 99%